Effect of Pien Tze Huang on Lymphangiogenesis Mediated by LncRNA-ANRIL in Colorectal Cancer - Yao LU; Min ZHANG; Jie LIU; Qianqian MAO; Zhiyun CAO; Jiumao LIN (康复学报)
Objective:To evaluate the inhibitory effect and mechanism of Pien Tze Huang (PZH) on long non-coding RNA-ANRIL(LncRNA-ANRIL) mediated lymphangiogenesis in colorectal cancer (CRC) in vitro.Methods:HCT-116 cells were cultured in vitro, and divided into control group and PZH group (treated with 0.25, 0.50, 0.75 mg/mL). CCK-8 assay was used to evaluate cell ability. The expression of LncRNA-ANRIL was detected by RT-qPCR, and the expression of VEGF-C was examined by Western blot. HCT-116 cells were transfected with Lipofectamine RNAiMAX and divided into Si-NC and Si-ANRIL groups. RT-qPCR was used to detect the expression of LncRNA-ANRIL. Phase-contrast microscope was used to observe the cell morphology. CCK-8 assay was used to detect cell viability. Western blot was used to detect the expression of VEGF-C protein. Treat HCT-116 cells with Si-NC, Si-ANRIL and Si-NC+PZH(0.25 mg/mL) respectively and collect cell culture supernatants (Tumor culture supernatants, TSNs) for theculture of human lymphatic endothelium cell (HLEC). CCK-8 assay was used to detect cell proliferation, cell migration and invasion were evaluated by Transwell assay. Tube Formation assay was used to observe lymphatic vessel formation ability.Results:Treatment of HCT-116 cells with different doses of PZH significantly inhibited the viability (P< 0.01). At the same time, PZH treatment in HCT-116 cells also reduced the expression of LncRNA-ANRIL(P< 0.01) and the expression of VEGF-C protein in a dose-dependent. Silencing LncRNA-ANRIL in HCT-116 cells, compared with Si-NC group, the expression of LncRNA-ANRIL in Si-ANRIL group was significantly reduced (P< 0.05), and the expression of cell density, cell viability (P< 0.01) and VEGF-C protein was also decreased. After the collected TSNssupernatant was used to treat HLEC cells, compared with the Si-NC group, Si-ANRIL and Si-NC+PZH(0.25 mg/mL) groups could remarkably decrease HLEC cell viability, migration and invasion ability and tube formation ability (P< 0.01).Conclusion:PZH can inhibit the expression of LncRNA-ANRIL in colorectal cancer cells and its mediated lymphangiogenesis in colorectal cancer. LncRNA-ANRIL is one of the targets of PZH in inhibiting lymphangiogenesis in colorectal cancer.